NILAI-NILAI ISLAM DALAM DRAMA KOREA PERSPEKTIF ANAK MUDA MUSLIM PEKANBARU - Imron Rosidi; Masduki Masduki; Dony Arung Triantoro (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article describes one of the effects of globalization on young Muslims in Indonesia. This article argues that the emergence of globalization has provided opportunities for young Muslims to take 'Islamic' values from the non-Arab world, not solely from the center of Islam (Muslim Arab countries). The purpose of this study is to find out how Pekanbaru Muslim Youth take Islamic values contained in Korean drama. This research uses ethnographic methods, by identifying informants namely young Muslim Muslims who are pious from Islamic educational backgrounds and like Korean television dramas. They have a good understanding of Islam so that in daily life they used to do the obligatory prayers five times a day and fasting is obligatory in the holy month of Ramadan. Even some of them do the teachings of Islam that are sunnah such as reading the Qur'an, sunnah prayers in congregation in the mosque and others. This article found that Korean television dramas encourage Muslim young people to negotiate Islamic values displayed in Korean television dramas. The results of this study reveal some Islamic values such as aspects of hard work, and never give up are often portrayed in television dramas.